Women, Signs, and Struggles in Norah: A Semiotic Exploration of Tawfik Al-Zaidy’s Film - Rika Rahmawati; Rohanda Rohanda; Asep Supianudin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study examines the representation of women’s struggle in the film Norah directed by Saudi Arabian filmmaker Tawfik Al-Zaidi using Charles Sanders Peirce’s semiotic approach. The research addresses two main problems, namely the forms of women’s struggle and the meanings of those struggles as represented in the film. This study aims to identify the forms of women’s struggle and to interpret their meanings through a semiotic perspective. This research employs a descriptive qualitative method using visual and verbal data obtained from selected scenes in the film. The analysis is conducted by applying Peirce’s triadic model, which consists of representamen, object, and interpretant, to understand the process of meaning-making in the representation of women’s struggle. The results show that the main character’s struggles are categorized into three forms: social, economic, and existential struggles. These struggles are reflected in the character’s efforts to confront social norms and pressures, to seek recognition and independence, and to understand as well as assert her identity as an individual. Overall, women’s struggle in this film is interpreted as a gradual process, starting from awareness of limitations, developing into the courage to resist, and eventually leading to self-acceptance and recognition. This study contributes to the discourse on women’s representation in Arab cinema, particularly in understanding women’s struggles within Middle Eastern cultural contexts, and reinforces the application of Peirce’s semiotic theory in film analysis as a medium of social and cultural representation.